Abnormalities of the spleen in relation to congenital malformations of the heart: a survey of necropsy findings in children. Issue 2 (February 1990) - Anderson, C; Devine, W A; Anderson, R H; Debich, D E; Zuberbuhler, J R
Abstract : A series of 1042 reports of necropsies on children dying at Children's Hospital of Pittsburgh was reviewed. In each case, note was taken of the status of the spleen, the lobation of the lungs, the arrangement of the bronchi, the morphology of the atrial appendages, and the presence of any congenital malformations of the heart and great vessels and of any malformations of the abdominal organs. There was isomerism of the left atrial appendages in eight (0.77%), 13 (1.25%) showed isomerism of the right appendages, and seven (0.67%) had multiple spleens without having isomerism of the atrial appendages. Unexpectedly, a normal spleen was found in one patient with isomerism of the right appendages and also in a patient with isomerism of the left appendages. In one patient with isomeric left atrial appendages there was no spleen. The review showed that the morphology of the atrial appendages, and hence the arrangement of the atria, is not accurately predicted by the type of spleen. The arrangement of the atrial appendages is the most reliable guide to the recognised combinations of congenital cardiac malformations previously described as "splenic syndromes". Because there is no certain way of predicting all the malformations in patients with complex congenital heart disease, it is advisable to record separately for each patient the details of lobation of the lungs, the bronchial and atrial arrangement, anomalies of the heart and great vessels, the type of spleen, and any abnormal arrangement of the abdominal organs.